2014
DOI: 10.1001/jamaneurol.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Functional Brain Connectivity and Personality Traits in Myotonic Dystrophy Type 1

Abstract: IMPORTANCE Myotonic dystrophy type 1 (DM1), the most common muscular dystrophy observed in adults, is a genetic multisystem disorder affecting several other organs besides skeletal muscle, including the brain. Cognitive and personality abnormalities have been reported; however, no studies have investigated brain functional networks and their relationship with personality traits/disorders in patients with DM1. OBJECTIVE To use resting-state functional magnetic resonance imaging to assess the potential relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 44 publications
(53 reference statements)
5
67
1
7
Order By: Relevance
“…Impairment in the glutamatergic system among patients with DM1 might be associated with synaptic dysfunction as demonstrated in recent studies [23,25]. Moreover, our demonstration of synaptic dysfunction might be in agreement with a previous study showing impairment in brain connectivity among patients with DM1 [42], given synapses' important role in brain connectivity [43]. Because histopathological analysis of synaptosomes in a large region is not an appropriate method for detecting subtle changes throughout the brain, measurement in vivo by 1 H-MRS appears to have an advantage over it to detect such brain impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Impairment in the glutamatergic system among patients with DM1 might be associated with synaptic dysfunction as demonstrated in recent studies [23,25]. Moreover, our demonstration of synaptic dysfunction might be in agreement with a previous study showing impairment in brain connectivity among patients with DM1 [42], given synapses' important role in brain connectivity [43]. Because histopathological analysis of synaptosomes in a large region is not an appropriate method for detecting subtle changes throughout the brain, measurement in vivo by 1 H-MRS appears to have an advantage over it to detect such brain impairment.…”
Section: Discussionsupporting
confidence: 93%
“…13,86 Abnormal resting-state functional connectivity in defaultmode and 'theory-of-mind' networks was also noted in relation to personality traits and social cognition in DM1 (table 3). 56,87 The most consistent finding in MRS studies was a decrease in N-acetylaspartate (NAA) (table 4). 8,17,35,62,88 Correlation of imaging with genetic and clinical parameters (95% CI = 63.8 to 76.5%); I 2 : 77%) of WMH across studies may be the result of study characteristics such as field strength (e.g.…”
Section: Structural Imaging Studiesmentioning
confidence: 85%
“…Nonetheless, it is likely that damage to structural brain networks results in alterations in functional connectivity that has recently been demonstrated in DM1. 56,87 These studies are critically important for better understanding of imaging correlates of neuropsychological involvement in DM1. The lack of consistent correlations found to date may result from limited power due to small sample sizes, and from the fact that cognitive functions are not anatomically set to one particular brain region, but rather are a consequence of complex network interactions.…”
Section: Structural Imaging Studiesmentioning
confidence: 99%
“…The progression of DM1 is often marked by cognitive dysfunction,10 which may influence adherence to NIV treatment, the risk of NIV-related complications and symptom control. Furthermore, a study has shown low sensitivity to hypercapnia among patients with DM1 11.…”
Section: Discussionmentioning
confidence: 99%